How Behaviorism Shaped a New Department Chair's Approach to Leadership - Diane Myers (Academic Chairpersons Conference Proceedings, 2019)
During this presentation, a second-year department chair will discuss how her background in behaviorism (specifically, in positive behavior interventions and supports) shaped her approach to working with faculty. She will share successes, not-quite-successes, and other lessons learned from implementing a behavioral approach to leadership.
Keywords: leadership; behavioral perspective; PBIS; lessons learned